PERAN KETERBUKAAN INFORMASI PUBLIK DALAM ADMINISTRASI PEMERINTAHAN DESA - Nuriyatman, Eko; Mushawirya, Rustian; Fitria, Fitria; Hartati, Hartati; Repindowaty Harahap, Rahayu (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Batang Sangir Village is a village located in Kayu Aro District, Kerinci Regency. However, it is regrettable that until now Batang Sangir Village does not have an official website which is the gateway to the availability of information in the village and can be accessed by the entire community. To find out the organizational structure of the village government, village potential, village regulations, and all matters related to the openness of public information that the community can access. In this Community Service activity, the team provided material related to the mandate of Article 24 of the Village Law, which contains 11 principles in implementing village government including those related to openness and accountability in implementing village government. This is also reinforced in Article 26 paragraph (4) letter (f) and letter (p) related to providing information to the village community. The village community is also given legal certainty as contained in Article 68 paragraph (1) related to obtaining information from the village government. This must be done because the village is a public body, following Article 1 number 3 of the Information Commission Regulation concerning Village Public Information Service Standards. Participants in this activity consisted of all village officials, neighborhood association heads, youth organizations, and all neighborhood association heads in Batang Sangir Village. With this activity, it is hoped that the village government will immediately create a website for the sake of openness of village information that can accessed anywhere by the community.